Download presentation
Presentation is loading. Please wait.
Published byLuke Banks Modified over 8 years ago
1
8.1-2 – Exponential Functions
2
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range.
3
*Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83!
4
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range. *Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83!
5
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range. *Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83! xy -20.25 0.5 01 12 24
6
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range. *Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83! xy -20.25 0.5 01 12 24
7
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range. *Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83! xy -20.25 0.5 01 12 24
8
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range. *Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83! xy -20.25 0.5 01 12 24
9
Ex. 1 Sketch the graph of y = 2 x. Then state the functions domain & range. *Sketch of graph must have y-intercept & four other coordinate points. Use the “table” function on your TI- 83! xy -20.25 0.5 01 12 24
10
Ex. 2 Sketch the graph of y = (⅞) x. Then state the functions domain & range.
11
xy -21.3061 1.1429 01 10.875 20.76563
12
Exponential Growth – for any equation in the form y = a x, a > 1
13
Exponential Decay – for any equation in the form y = a x, a < 1
14
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay.
15
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x
16
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth
17
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x
18
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay
19
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x
20
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x
21
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x growth
22
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x growth d. y = 4 -x
23
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x growth d. y = 4 -x = 1 4 x
24
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x growth d. y = 4 -x = 1 = 1 x 4 x 4
25
Exponential Growth – for any equation in the form y = a x, a > 1 Exponential Decay – for any equation in the form y = a x, a < 1 Ex. 3 Determine whether each exponential function represents exponential growth or decay. a. y = 7 x growth b. y = (0.5) x decay c. y = 0.3(5) x growth d. y = 4 -x = 1 = 1 x decay 4 x 4
26
Ex. 4 Solve each equation. a. 3 x = 3 2
27
Ex. 4 Solve each equation. a. 3 x = 3 2
28
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2
29
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81
30
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81
31
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81
32
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 ?
33
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4
34
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4
35
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4
36
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64
37
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64
38
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64
39
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6
40
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6
41
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6
42
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1
43
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓
44
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1
45
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1
46
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1
47
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1
48
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1 4 -x = 4 2(2x + 1)
49
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1 4 -x = 4 2(2x + 1) 4 -x = 4 4x + 2
50
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1 4 -x = 4 2(2x + 1) 4 -x = 4 4x + 2
51
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1 4 -x = 4 2(2x + 1) 4 -x = 4 4x + 2 -x = 4x + 2
52
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1 4 -x = 4 2(2x + 1) 4 -x = 4 4x + 2 -x = 4x + 2 -5x = 2
53
Ex. 4 Solve each equation. a. 3 x = 3 2 x = 2 b. 3 x = 81 3 x = 3 4 x = 4 c. 2 3x + 5 = 64 2 3x + 5 = 2 6 3x + 5 = 6 3x = 1 x = ⅓ d.(¼) x = 16 2x + 1 4 -x = 16 2x + 1 4 -x = (4 2 ) 2x + 1 4 -x = 4 2(2x + 1) 4 -x = 4 4x + 2 -x = 4x + 2 -5x = 2 x = -2/5
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.